ANALISA ASUHAN KEPERAWATAN PADA IBU POST SECTIO CAESAREA PRIMIPARA DENGAN PIJAT OKSITOSIN UNTUK MENINGKATKAN PRODUKSI AIR SUSU IBU - Rizki Nur Azizah, (2023)
Analysis of nursing care for primiparous post sectio caesarean mothers with oxytocin massage to increase breast milk production at Pasar Minggu Regional General Hospital which aims to determine the effectiveness of oxytocin massage therapy on the release and smoothening of breast milk in primiparous post SC mothers.The assessment was conducted on November 14, 2022 to Mrs. F with Post Caesarean in the jasmine room on the 7th floor of Pasar Minggu Hospital. The data obtained comes from primary data obtained directly from the patient and secondary data, namely data obtained from the family and the nurse's progress notes in the jasmine room.The results of the assessment obtained from primary and secondary data related to managed patients and resumes. The managed patient is Mr. Mr. F with age 22 years P1A0 gave birth by section caesarea for indications of cephalopelvic disproportion (CPD). Implementation carried out by managed patients and resume patients is to overcome the problem of ineffective breastfeeding related to the inadequacy of breast milk supply, according to the SIKI book and Evidaance Based Nursing (EBN), namely the oxytocin massage is a massage performed in the back area to increase the production and release of breast milk.